2018
DOI: 10.1111/pcn.12735
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Wernicke's encephalopathy in anorexia nervosa: A systematic review

Abstract: Anorexia nervosa (AN) is a common eating disorder that affects 2.9 million people worldwide. Not eating a balanced diet or fasting can cause neurological complications after severe vitamin B1 malnourishment, although the precise signs and symptoms of Wernicke's encephalopathy (WE) are not clear. Our aim was to review the signs and symptoms of WE in patients with AN. We searched MEDLINE, EMBASE, Scopus, and PiCarta on all case descriptions of WE following AN. All case descriptions of WE in AN, irrespective of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 38 publications
2
48
0
2
Order By: Relevance
“…In modern society, KS is often caused by severe alcoholism and self-neglect leading to thiamine depletion (Kopelman, Thomson, Guerrini, & Marshall, 2009). Other causes of thiamine deficiency can lead to KS, such as extreme vomiting after obesity surgery, anorexia nervosa, and multiple forms of cancer (Isenberg-Grzeda, Rahane, DeRossa, Ellis, & Nicolson, 2016;Oudman, Wijnia, Oey, van Dam, & Postma, 2018b;Oudman, Wijnia, van Dam, Biter, & Postma, 2018a). KS is characterized by severe cognitive problems, such as explicit memory deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…In modern society, KS is often caused by severe alcoholism and self-neglect leading to thiamine depletion (Kopelman, Thomson, Guerrini, & Marshall, 2009). Other causes of thiamine deficiency can lead to KS, such as extreme vomiting after obesity surgery, anorexia nervosa, and multiple forms of cancer (Isenberg-Grzeda, Rahane, DeRossa, Ellis, & Nicolson, 2016;Oudman, Wijnia, Oey, van Dam, & Postma, 2018b;Oudman, Wijnia, van Dam, Biter, & Postma, 2018a). KS is characterized by severe cognitive problems, such as explicit memory deficiencies.…”
Section: Introductionmentioning
confidence: 99%
“…The RDI for thiamine for patients admitted to the adolescent ward ranges from 1.1 mg/day -1.2 mg/day, depending on gender and age [29], and the multivitamin alone provided patients with 10 mg of thiamine daily (approximately 10 times the RDI). Comparison of these findings to other studies is difficult because the amount of thiamine consumed from oral intake and enteral feeds is not being routinely reported [18,19].…”
Section: Discussionmentioning
confidence: 86%
“…This practice is based on foundation knowledge of the role of thiamine as an essential cofactor in carbohydrate metabolism, an essential pathway during refeeding [2], and previous research demonstrating thiamine supplementation prior to nutritional rehabilitation may prevent TD and its associated neuropsychiatric conditions WE and WKS [16,17]. A study of 37 patients with AN reported a 38% prevalence of TD [18], and a systematic review by Oudman E et al (2018) identified 12 cases of TD causing WE in patients with AN ranging from BMI 12.2 kg/m 2 to 17.4 kg/m 2 , including some patients with a history of alcohol and substance abuse [19].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that rapid weight loss and malnutrition can result in WE, and the occurrence of WE is directly linked to rapid weight loss. [ 11 , 12 ]…”
Section: Discussionmentioning
confidence: 99%